Juridical Overview of Land Dispute Settlement - Misbakhul Munir; Azis Budianto; Rineke Sara (Publikasiku, 2023)
Along with the times, the way people view land slowly began to change. In the past, land was only considered a supporting factor for agricultural activities, but now it has been seen from a more strategic perspective, namely as an important asset in the world of industry and human life. Now a lot of lands has been used not only as a place for agricultural activities but also for industrial activities, including being used as an integrated residential complex such as housing which has recently mushroomed everywhere. Settlement of land dispute cases as regulated in Law Number 51 of 1960, in article 2 and article 6 paragraph (1) letter a, that the use of land without permission from those who are entitled or their legal proxies is a prohibited act and is threatened with criminal penalties. However, in responding to conflicts and land disputes that arise, one must look at it from several points of view while still prioritizing justice and not harming both parties, so it is not only seen from the side of the occupation, but also in terms of the utilization and use of the land by the community owner if in terms of utilization the land is not utilized optimally and even seems to have been neglected by the owner for approximately 15 years. Settlement of disputes through deliberation with mediation is taken as a path to resolving land problems, considering that the main purpose of mediation is to resolve problems, not just applying norms or creating order, but its implementation must also be based on general principles.